P107 Decreased epithelial keratinization contributes to defective wound healing in Crohn's disease fistula. (30th January 2023) - Becker drs., M; Koelink, P; Bemelman, W; D'Haens, G; Buskens, C; Wildenberg, M
Abstract: Background: Up to 30% of Crohn's Disease (CD) patients suffer from perianal fistula creating a high disease burden. Treating CD fistula is challenging compared to cryptoglandular fistula, which have a significantly better wound healing response. Previous studies suggested epithelial to mesenchymal transition as an inducer of fistula formation, as markers were observed in fistula tracts. However, most studies compared CD fistula to normal mucosa, thus disregarding whether any observed difference was in fact a sign of healing (as CD fistula will have more active healing than uninjured mucosa) or a sign of pathology (as healing is not occurring effectively). Therefore, in this study we evaluated CD fistula, as well as both healthy mucosa (no active healing) and cryptoglandular fistula (effective healing) in order to determine the role of differences found. Methods: Biopsies from the internal opening (n=20) of perianal fistula of CD patients were collected and compared to two publicly available datasets obtained from un-inflamed rectum (RISK cohort and GSE83245). In addition, curettage material of CD (n=54) and cryptoglandular fistula (n=15) was obtained. Expression profiling was performed using RNASeq. Results: Comparing the mucosa at the internal opening of CD fistula to publicly available datasets of healthy rectum, 770 genes were differentially expressed. Pathway analysis revealed upregulation of proliferative and inflammatory processes, consistent with expected immune and wound healing responses. Interestingly, strongest upregulation was seen for processes of cornification and keratinization, including expression of IVL (involucrin) and FLGR2 (fillagrin2), involved in keratinocyte differentiation. To evaluate whether this was contributing to active wound healing or rather to persistent disease, we analyzed the actual tract in CD and cryptoglandular fistula. Strikingly, cornification and keratinization processes were more pronounced in cryptoglandular fistula, suggesting a role in effective healing rather than the persistent pathology seen in CD. Similar data was observed for TGFb, previously detected in CD fistula and thus considered a pathological contributor. While we confirm increased TGFb activity in CD fistula compared to normal mucosa, activity in cryptoglandular fistula tracts was higher than in CD fistula tracts. Again, this would suggest TGFb signaling as part of the wound healing response rather than part of the pathogenic mechanism. Conclusion: Perianal fistulas show upregulation of keratinization and cornification pathways compared to healthy mucosa. Comparing CD and cryptoglandular fistula, we saw more cornification in the better healing cryptoglandular fistula, suggesting involvement in effective healing rather than pathology.